Limiting conflicts when managing public lands for furbearer trapping and dog‐related recreation - Heather A. Triezenberg; Barbara A. Knuth (Wildlife Society Bulletin)
ABSTRACT Resource users with different interests frequent public lands, resulting in opportunity for conflict. We examined the issue of interactions among wildlife trappers and dog owners by examining stakeholders’ socio‐demographics, land usage, concerns, attitudes, and satisfaction with multiuse public land management for recreation with dogs and furbearer trapping. We sent mail‐back questionnaires to licensed dog owners (n = 1,000; hereafter, dog owners) and licensed wildlife trappers (n = 1,000; hereafter, wildlife trappers) in a 10‐county area of New York, USA, during 2009. After weighting data, results revealed dog owners and wildlife trappers had differences in land usage patterns for all land types. Dog owners and wildlife trappers, regardless of whether they owned a dog, differed in all items except that they had similar levels of satisfaction for management of public lands in their region for both recreation with dogs and wildlife trapping. Seeing dogs under voice and sight command of their owner or trainer was positively related to satisfaction with management of public lands for wildlife trappers and agreement that dog owners have few places to take their dogs and allow them to run off‐leash. Concern about dogs getting caught in wildlife traps was negatively related to satisfaction with public lands management for wildlife trappers. For dog owners, agreement that trappers should be allowed to trap on public lands was positively related to satisfaction. Our results suggest that state wildlife agencies seeking to improve stakeholder interactions and satisfaction with public land management for both wildlife trapping and recreation with dogs should promote the importance of dogs being under control through voice or sight command or directly on a leash, and should consider creating spaces for dogs to run off leash. © 2018 The Wildlife Society.